2016
DOI: 10.1007/s10120-016-0669-2
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor stromal proportion predicts aggressive phenotype of gastric signet ring cell carcinomas

Abstract: Objective The aim of this study was to evaluate the prognostic significance of the intratumor stromal proportion in gastric signet ring cell (SRC) carcinomas. Background Cancer stroma, as exemplified by cancer-associated fibroblasts (CAFs), plays critical roles in cancer proliferation, invasion, and metastasis. Methods One hundred seventy-five SRC carcinoma cases were classified according to the intratumor desmoplastic stromal proportion to then analyze the clinicopathologic characteristics of stroma-rich case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 32 publications
5
67
1
Order By: Relevance
“…The study by Lee et al suggests that there could be a relationship between PoT and disease stage as in multivariate analysis the prognostic significance of the stroma proportion was only seen in GC patients with T3/4 disease. Furthermore, low PoT was seen in 8% of stage I patients and in up to 69% of stage III patients . While we measured PoT using a quantitative morphometric method, previous investigators simply visually estimated PoT which might explain the differences in the median PoT between studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The study by Lee et al suggests that there could be a relationship between PoT and disease stage as in multivariate analysis the prognostic significance of the stroma proportion was only seen in GC patients with T3/4 disease. Furthermore, low PoT was seen in 8% of stage I patients and in up to 69% of stage III patients . While we measured PoT using a quantitative morphometric method, previous investigators simply visually estimated PoT which might explain the differences in the median PoT between studies.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is necessary to point out that the three previous GC studies evaluating the prognostic value of the proportion of stroma, but also studies investigating the same in colorectal cancer and other cancers all describe that a high proportion of stroma (eg, low PoT) is related to poor survival. Our study showed the opposite for the subgroup of intestinal‐type GC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CAFs are known to actively promote proliferation and differentiation of tumor cells as well as support angiogenesis and metastasis by promoting matrix remodeling and epithelial to mesenchymal transition (EMT) (106108). Even the enrichment of stroma/CAFs within the tumor tissue has a direct correlation with the tumor size and a negative impact on the clinical prognosis (109)—as observed in cases of gastric signet ring cell carcinoma—indicating the profound impact of CAFs on overall tumor biology.…”
Section: Metabolism Of the Components Of Tmementioning
confidence: 99%